A Research and Development (R&D) roadmap for influenza vaccines: Looking toward the future - Moore, K.A.; Ostrowsky, J.T.; Kraigsley, A.M.; Mehr, A.J.; Bresee, J.S.; Friede, M.H.; Gellin, B.G.; Golding, J.P.; Hart, P.J.; Moen, A.; Weller, C.L.; Osterholm, M.T.; et al. (Vaccine, 2021)
Improved influenza vaccines are urgently needed to reduce the burden of seasonal influenza and to ensure a rapid and effective public-health response to future influenza pandemics. The Influenza Vaccines Research and Development (R&D) Roadmap (IVR) was created, through an extensive international stakeholder engagement process, to promote influenza vaccine R&D. The roadmap covers a 10- year timeframe and is organized into six sections: virology; immunology; vaccinology for seasonal influenza vaccines; vaccinology for universal influenza vaccines; animal and human influenza virus infection models; and policy, finance, and regulation. Each section identifies barriers, gaps, strategic goals, milestones, and additional R&D priorities germane to that area. The roadmap includes 113 specific R&D Abbreviations: ABS, Access and Benefit Sharing; ACT, Access to COVID-19 Tools; ADCC, antibody-dependent cellular cytotoxicity; CARB-X, biopharmaceutical accelerator for combating antibiotic resistant bacteria; CEPI, Coalition for Epidemic Preparedness Innovations; CIDRAP, Center for Infectious Disease Research and Policy; CIVICs, Collaborative Influenza Vaccine Innovation Centers; COBRA, computationally optimized broadly reactive antigen; CHIVIM, controlled human influenza virus infection model; EU, European Union; FVVA, full value of vaccine assessment; GISRS, Global Influenza Surveillance and Response System; HAI, hemagglutination-inhibition; HA, hemagglutinin; HVAC, heating, ventilation, and air conditioning; IIV, inactivated influenza vaccines; IVR, Influenza Vaccines Research and Development (R&D) Roadmap; LAIV, live-attenuated influenza vaccines; LMICs, low- and middle-income countries; ME&A, monitoring, evaluation, and adjustment; NA, neuraminidase; NIAID, US National Institute of Allergy and Infectious Diseases; R&D, Research and Development; SME, subject matter expert; WHO, World Health Organization.
Research Article
Keywords: Influenza; Pandemic preparedness